Adoptive transfer of immunomodulatory M2 macrophages suppresses experimental autoimmune encephalomyelitis in C57BL/6 mice via blockading NF-κB pathway. (1st February 2021) - Chu, F; Shi, M; Lang, Y; Chao, Z; Jin, T; Cui, L; Zhu, J
Summary: Macrophages play important roles in multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), and M2 macrophage may have anti-inflammatory effects. In this study, we elucidated the roles of M1 and M2 macrophages in the pathogenesis of EAE and the effects of treatment with M2 macrophages that target certain proinflammatory cytokines and with immunomodulatory preparations that beneficially influence the disease course. We found macrophages increased at the onset of clinical signs in the EAE group, consistent with an increased proportion of M1 macrophages and low numbers of M2 macrophages. As the disease progressed and the symptoms worsened, M1 macrophages decreased and M2 macrophages gradually increased until the peak. In the recovery stage, M2 macrophages gradually decreased. Treatment with M2 macrophages inhibited the nuclear factor kappa B (NF-κB) pathway, alleviated the symptoms of EAE, reduced inflammatory cell infiltration and demyelination in the central nervous system and decreased the numbers of macrophages in the spleens. BAY-11-7082, an NF-κB blocking agent, could reduce the total number of macrophages both in vivo and in vitro, effectively prevented EAE development and significantly inhibited EAE symptoms in mice. Our study demonstrates that macrophages may play a crucial role in the pathogenesis of EAE, while M2 macrophages have anti-inflammatory effects. Transfer of M2 macrophages to EAE mice can block the NF-κB pathway successfully and relieve EAE symptoms. Application of NF-κB blockers is useful in the prevention and treatment of EAE. Graphical Abstract: